Utilization Of Frozen Goat Semen With Addition Sweet Orange Essential Oil To Improve Genetic Quality in Ujung Teran Village - Sitepu, Sukma Aditya; Julia Marisa (Journal of Saintech Transfer, 2019)
One of the causes of underdeveloped goats is low genetic quality. The way that can be done to improve the genetic quality of goats is to do cross-breeding with superior goats through Artificial Insemination. The community service aims to increase the knowledge of goat farmers in Ujung Teran Village, Langkat Regency on how to make goat frozen semen using tris yolk extender plus sweet orange essential oil for Artificial Insemination program along with the benefits that can be obtained. The method of service is by giving lectures and training to goat farmers. The results obtained from the implementation of this program are that farmers know how to make frozen semen of goat using sweet orange essential oil on the tris yolk extender and are willing to make Artificial Insemination in their goat cattle.